2001
DOI: 10.1095/biolreprod64.1.331
|View full text |Cite
|
Sign up to set email alerts
|

Female Steroid Hormones Modulate Receptors for Nerve Growth Factor in Rat Dorsal Root Ganglia1

Abstract: Calcitonin gene-related peptide (CGRP) is a vasodilatory peptide, and it is primarily synthesized in dorsal root ganglia (DRG). Plasma CGRP levels increase during pregnancy and with steroid hormones, and nerve growth factor (NGF) stimulates calcitonin/CGRP promoter and CGRP synthesis in DRG. We previously showed that CGRP levels in DRG were stimulated with steroid hormone treatments in vivo but not in vitro. Thus, the stimulation of CGRP by these hormones may be indirect through the upregulation of NGF effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 56 publications
5
39
0
4
Order By: Relevance
“…The first mechanism is via binding of the sex steroid molecules to associated receptors (estrogen receptor α/β, androgen receptor, progesterone receptor) which then bind to discrete response elements on DNA and mediate transcription or repression of target genes (Truss and Beato, 1993) including, but not limited to: neurotransmitter receptor sub-units (Cyr et al, 2000;D'Souza et al, 2003), trkA and p75 NTR receptors (Lanlua et al, 2001), and peripheral myelin proteins (Melcangi et al, 2000). The second mechanism of action of gonadal hormones is via binding of the steroid molecules to membrane-associated receptors which signal through a variety of intracellular signaling cascades (Moggs and Orphanides, 2001;Simoncini and Genazzani, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The first mechanism is via binding of the sex steroid molecules to associated receptors (estrogen receptor α/β, androgen receptor, progesterone receptor) which then bind to discrete response elements on DNA and mediate transcription or repression of target genes (Truss and Beato, 1993) including, but not limited to: neurotransmitter receptor sub-units (Cyr et al, 2000;D'Souza et al, 2003), trkA and p75 NTR receptors (Lanlua et al, 2001), and peripheral myelin proteins (Melcangi et al, 2000). The second mechanism of action of gonadal hormones is via binding of the steroid molecules to membrane-associated receptors which signal through a variety of intracellular signaling cascades (Moggs and Orphanides, 2001;Simoncini and Genazzani, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Because the ratio of the maximal plasma levels of estrogen with respect to that of P4 during proestrus is ϳ1:1,000 (44), we used 5 mg P 4. Furthermore, these doses have been previously reported to produce estrogenic and progestogenic responses in the reproductive tract (20) and other organs (29).…”
Section: Methodsmentioning
confidence: 95%
“…Animal studies have also shown that surgical ovariectomy increases the expression of p75 NTR , while decreasing TrkA, at both mRNA and protein levels. These effects are completely abrogated by exogenous estrogens [51,80,89,123]. Therefore, the loss of ovarian function after menopause would only aggravate the age-associated changes in neurotrophin receptors, further increasing the risk for AD in normally aging women.…”
Section: Igf1-r Neurotrophin Signaling and Ad: A Tale Of Receptors mentioning
confidence: 99%